Case report: Recurrent hypokalemic periodic paralysis associated with distal renal tubular acidosis (type 1) and hypothyroidism secondary to hashimoto´s thyroiditis - Meregildo Rodriguez, Edinson Dante (2019)
Background: Hypokalemic periodic paralysis (HypoKPP) is characterized by transient episodes of flaccid muscle weakness. We describe the case of a teenaged boy with HypoKPP and hyperthyroidism due to Hashimoto's thyroiditis with initial manifestation of renal tubular acidosis. This combination is rare and little described previously in men. Case presentation: A 17-year-old boy was admitted after three days of muscular weakness and paresthesia in the lower limbs with an ascending evolution, leading to prostration. Decreased strength was found in the lower limbs without a defined sensory level, reduced patellar and ankle reflexes. Positive antithyroid antibodies were found. He received hydration treatment, IV potassium and levothyroxine, with which there was a clinical improvement. Other examinations led to the diagnosis of type 1 renal tubular acidosis. Conclusion: HypoKPP is a rare disorder characterized by acute episodes of muscle weakness. Type 1 renal tubular acidosis can occur as a consequence of thyroiditis, which is explained by the loss of potassium. This combination is unusually rare, and has not been described before in men. The etiopathogenesis of the disease as well as a dynamic explanation of what happened with the patient are discussed in this report.